Effect of an Electromagnetic Field on Anaerobic Digestion: Comparing an Electromagnetic System (ES), a Microbial Electrolysis System (MEC), and a Control with No External Force - Nhlanganiso Ivan Madondo; Emmanuel Kweinor Tetteh; Sudesh Rathilal; Babatunde Femi Bakare (Molecules, 2022)
This study examined the application of an electromagnetic field to anaerobic digestion by using an electromagnetic system (ES), a microbial electrolysis cell (MEC), and a control with no external force. The experimental work was performed by carrying out biochemical methane potential (BMP) tests using 1 L biodigesters. The bioelectrochemical digesters were supplied with 0.4 V for 30 days at 40 °C. The electromagnetic field of the ES was generated by coiling copper wire to form a solenoid in the BMP system, whereas the MEC consisted of zinc and copper electrodes inside the BMP system. The best performing system was the MEC, with a yield of 292.6 mL CH4/g chemical oxygen demand removed (CODremoved), methane content of 86%, a maximum current density of 23.3 mA/m2, a coulombic efficiency of 110.4%, and an electrical conductivity of 180 µS/cm. Above 75% removal of total suspended solids (TSS), total organic carbon (TOC), phosphate, and ammonia nitrogen (NH3-N) was also recorded. However, a longer exposure (>8 days) to higher magnetic intensity (6.24 mT) on the ES reduced its overall performance. In terms of energy, the MEC produced the greatest annual energy profit (327.0 ZAR/kWh or 23.36 USD/kWh). The application of an electromagnetic field in anaerobic digestion, especially a MEC, has the potential to maximize the methane production and the degradability of the wastewater organic content.